1985
DOI: 10.1002/chin.198525335
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS AND CHARACTERIZATION OF CATIONIC GOLD‐IRIDIUM CLUSTERS. STRUCTURE OF (IRAU2(H)(PPH3)4NO3)BF4

Abstract: Bei der Umsetzung von Au(PPh3)NO3 mit [Ir(PPh3)2(H)2((CI‐I3)2CO)2]BF4 in Aceton wird bei ‐78°C die Verbindung (I), bei ‐ 10°C (II) und bei 25°C (III) gebildet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In complex 6 though, the Au(I) ion sits directly over the Ir(I) ion suggesting a Ir-Au interaction. However, it is clear no bond exists since the atoms are separated by 3.2770(3) Å, a distance that is well-outside the range reported for Ir-Au bonds of 2.59 Å-2.81 Å [53][54][55][56][57][58][59][60][61][62].…”
Section: 6mentioning
confidence: 84%
“…In complex 6 though, the Au(I) ion sits directly over the Ir(I) ion suggesting a Ir-Au interaction. However, it is clear no bond exists since the atoms are separated by 3.2770(3) Å, a distance that is well-outside the range reported for Ir-Au bonds of 2.59 Å-2.81 Å [53][54][55][56][57][58][59][60][61][62].…”
Section: 6mentioning
confidence: 84%
“…Much evidence has been garnered from study of the analogous quadruply bonded Mo2X4(PP)2 compounds to show that the a form is the kinetically favored product, while the ß form is obtained when the reaction proceeds to thermodynamic equilibrium.8 This is consistent with some recent observations on Re2X4(LL)2 systems: When Re2Cl4(depe)2 (depe is l,2-bis(diethylphosphino)ethane) was prepared by refluxing (n-Bu4N)2-[Re2Cl6] and depe in ethanol for several hours, /3-Re2Cl4(depe)2 was isolated as the only product. 13 The rate-determining step in this case appears to be the dissolving of the starting material since (n-Bu4N)2[Re2Cl8] is only slightly soluble in ethanol. On the other hand, in this study (zt-Bu4N)2[Re2Cl8] was reacted in methanol, where it is highly soluble, with dmpe, and a swift reaction was observed at room temperature with simultaneous precipitation of the product, a-Re2Cl4(dmpe)2.…”
Section: Resultsmentioning
confidence: 99%
“…The molecule possesses crystallographic 2/m symmetry with both rhenium atoms located on a mirror plane and the 2-fold axis being a perpendicular bisector of the Re-Re bond. The five-membered metallacycles formed by the chelating dmpe ligands are in an envelope con- (13) Campbell, F. L.; Cotton, F. A.; Powell, G. L. Inorg. Chem., in press.…”
Section: Resultsmentioning
confidence: 99%
“…Dinuclear Au-Rh [439][440][441] and Au-Ir [247,446,[461][462][463][464][465][466][467][468][469] compounds with both supported and unsupported Au-metal bonds have also been reported. An unsupported Au-Ir bond [2.607(2) Å] can also be considered for the linear, trinuclear complex [(Ph 3 P)AuIr 2 (dimen) 4 (PPh 3 )](PF 6 ) 3 , in which an Au(PPh 3 ) unit occupies one of the axial sites of the Ir 2 (dimen) 4 core, while a PPh 3 ligand is placed in the second axial position [470].…”
Section: Gold-group 9 Metal Compoundsmentioning
confidence: 99%
“…An unsupported Au-Ir bond [2.607(2) Å] can also be considered for the linear, trinuclear complex [(Ph 3 P)AuIr 2 (dimen) 4 (PPh 3 )](PF 6 ) 3 , in which an Au(PPh 3 ) unit occupies one of the axial sites of the Ir 2 (dimen) 4 core, while a PPh 3 ligand is placed in the second axial position [470]. It was suggested that mono-hydrogen-bridged Au(m-H)M bonds are longer than unbridged Au-M bonds [247,463]. (Figure 4.40d) [476], with a linear Au-Ir-Au skeleton.…”
Section: Gold-group 9 Metal Compoundsmentioning
confidence: 99%